Inclusive Early Childhood Education for Children With and Without Autism: Progress, Barriers, and Future Directions - Siller, Michael; Morgan, Lindee; Wedderburn, Quentin; Fuhrmeister, Sally; Rudrabhatla, Asha (Frontiers in Psychiatry, 2021)
Access to inclusive high-quality early childhood education (ECE) programs for young children with disabilities has been required by law for over 40 years, has been recommended by leading professional organizations, and has been emphasized in federal public policy initiatives. Yet, improvement in the rates of young children with disabilities experiencing inclusion has been limited. This review article consists of three parts. First, we identify and describe four barriers to wide-scale implementation of inclusive ECE programs for children with Autism Spectrum Disorders (ASD). These barriers include (1) the fragmented nature of the ECE system in the United States, (2) the age at which ASD is typically first diagnosed in the community, (3) the diverse presentation/support needs of children with ASD, and (4) the thoughts and feelings of parents of children without disability about inclusion. Second, we illustrate the role of university-affiliated laboratory and models programs in creating educational innovations in inclusive ECE for ASD. By describing nine leading programs, we highlight similarities and differences between programs, and capture the unique ways in which successful programs leverage resources and facilitators and address barriers (e.g., federal and state regulations, funding sources, community resources, institutional structures and priorities, professional orientation and training, access to families and staff). Finally, we propose ten future directions for a science program to advance the development, evaluation, and implementation of community-viable inclusive ECE programs for young children with ASD. For children with ASD who are 3 years and older, educational interventions are the only universal, federally-mandated, and publicly-funded services available. Future progress in developing effective, community-viable interventions for this population hinges upon our ability to unlock the potential of inclusive ECE classrooms.